Queer(y)ing aging—potentialities and problems in applying Queer Theory to studies of aging and later life - Andrew King; Matthew Hall (Frontiers in Sociology, 2023)
Queer Theory is a radically deconstructionist perspective within the humanities and social sciences. Since its initial emergence in the late 1980s and early 1990s in the field of sexualities studies, Queer Theory has increasingly been used to challenges normative notions of self, identity, temporality and the nature of being, more broadly. Whilst Queer Theory has been utilized, to some extent, in gerontology and aging studies, this article makes an original contribution to this endeavor, assessing the potentiality and problems with queer(y)ing three aspects of aging: chronology; cognition; and frailty and vulnerability. To achieve this, the article draws on ideas from some key Queer theorical writers, existing studies of queer aging and illustrates theoretical points with qualitative data collected from two LGBTQ+ projects to illustrate. The article also considers problems with Queer Theory in challenging normativities associated with aging. It is concluded that despite problems, Queer Theory remains an important and valuable theoretical approach for disturbing and challenging many of the norms and understandings that shape and constrain older LGBTQ+ people's lives, in particular, and therefore have importance for how we think and understand aging and later life sociologically.